Effect of Insulin Degludec Versus Insulin Glargine on Glycemic Variability in Patients With Renal Transplantation with Pre-existing Type 2 Diabetes Mellitus; A 1-year, Randomized, Treat-to-Target Pilot Trial (Iranian Journal of Kidney Diseases, 2021)
Introduction. This study hypothesized that the insulin Degludec may have benefit if used in management of diabetes mellitus after renal transplantation to achieve better control at the critical time of adjustment of immunosuppressive regimens during the first year post transplant. Methods. Fifty patients with Type 2 diabetes Mellitus after renal transplantation with stable serum creatinine with glycosylated hemoglobin (HbA1C) 7 to 11% were included in the study to receive either Insulin Degludec or Insulin Glargine. Fasting blood glucose, 2 hour post-prandial levels and (HbA1c), were measured at 12, 16, 26, 40, and 52 weeks after renal transplantation also hypoglycemic episodes were documented all through the study. Results. Despite both groups are matched as regards demographic and metabolic data, FPG, and 2h PPG were lower in insulin Degludec group all through the study. HbA1c most pronounced decline, occurred at 52th week of treatment in both groups. The most important clinically relevant finding in our study was that; the overall confirmed hypoglycemia rates and the rate of nocturnal confirmed hypoglycemia was significantly lower with Degludec treated group (P < .001). Conclusion. Insulin Degludec provides optimum glycemic control in in the first year post-renal transplant patients with significantly lower rate of hypoglycemia. DOI: 10.52547/ijkd.6131